Establishing baseline mastitis parameters on commercial New Zealand sheep milking farms : a thesis presented in partial fulfilment of the requirements for the degree of Doctor of Philosophy in Veterinary Science - Chambers, Greg (Massey University, 2026)
Like all dairy species, milk production in sheep depends on udder health, and mastitis (inflammation of the mammary glands, usually associated with infection), is one of the most important diseases of dairy animals. Mastitis negatively affects animal welfare, productivity and milk quality and is therefore an animal health priority for dairy sheep operations globally. Sheep milking has grown rapidly in New Zealand in the last 20 years. As a new industry, New Zealand lacks its own systematically collected data, forcing farmers and veterinarians to extrapolate from bovine research or studies conducted in overseas dairy sheep industries. Differences in breeds, environments, management systems and industry priorities mean that overseas findings may not be directly applicable to New Zealand. In the 2022-2023 season, a research project was conducted to establish baseline parameters for udder health and milk quality in New Zealand dairy sheep. The objectives were to determine the incidence of clinical mastitis, the prevalence of subclinical mastitis and the bacterial causes of both; establish how clinical mastitis is treated and the outcomes that are achieved; characterise udder and teat conformation and health; describe ewe and bulk milk somatic cell counts and aerobic plate count; find somatic cell count thresholds for diagnosing intramammary infection (infection of the mammary tissue); explore the use of the rapid mastitis test and its correlation with somatic cell count; identify key risk factors for mastitis and elevated aerobic plate count; and determine associations between bulk milk somatic cell count and aerobic plate count. The research was conducted on 20 commercial farms spread from North Waikato to Canterbury, purposively selected to represent a range of farm systems. These 20 farms comprised approximately half of the commercial dairy sheep farms in operation at the time. Farmer interviews were conducted to collect descriptive and risk factor data. Clinical mastitis data and milk samples were collected by farm staff as cases were diagnosed according to a standardised definition (a change in the appearance of milk and/or signs of inflammation in the gland). Separately to this farmer work, the research team visited each farm at three points in the season, coinciding with early, mid and late lactation. Approximately 15 lactating ewes were randomly selected on each farm. Four udder morphology measures were scored on a 5-point scale: depth (the distance between the udder cleft and the abdominal wall), suspension (ratio of the width at the abdominal attachment to the height), separation (the extent of the udder cleft), and teat placement (determined from the vertical distance between the teat attachments and the most distal point of the udder). Teat length and width were measured. Teats and udders were assessed for presence of visible teat/udder inflammation, lesions and teat end hyperkeratosis, palpable consistency and lesions. The presence of a supernumerary teats and non-lactating glands (“half udders”, subjectively judged to be producing a small volume of milk compared to the contralateral gland, or to be non-lactating) were recorded. Milk samples were collected to conduct the rapid mastitis test and measure somatic cell count, aerobic plate count and perform bacterial culture. Bulk milk somatic cell count and aerobic plate count data were collected from the 16 farms that sent milk to a processor. Subclinical mastitis was defined at the ewe level as a ewe having one or two bacteriologically positive glands and a SCC >500,000 cells/mL and/or a RMT score ≥1. Clinical mastitis data were collected for 236 cases and randomly selected ewe data were collected from a total of 893 ewes. Farm practices varied widely, both between farms but also within farms across the season. Milk recording was only performed on 7/20 (35%) of study farms and ewe-level data were incomplete or absent on many farms. Wearing gloves during milking was mandatory on 40% of farms, and teat disinfection was used all season on 40% of farms. The morphology of the ewe teats and udders was similar to that observed in overseas dairy sheep and varied substantially between farms, while pathology was rare, with all conditions having a prevalence <6%. Clinical mastitis had a low incidence (2.3%) compared to New Zealand dairy cows, but consistent with overseas estimates for dairy ewes. While the incidence was low, clinical mastitis could be severe, with 25% of affected ewes having a fever and an overlapping 26% having depression, and only 15% of ewes recovering without lasting sequelae. Nearly half of all the clinical mastitis milk samples were culture negative. Including those in the denominator, 𝘚𝘵𝘳𝘦𝘱𝘵𝘰𝘤𝘰𝘤𝘤𝘶𝘴 𝘶𝘣𝘦𝘳𝘪𝘴 (14%), non-aureus staphylococci (12%), and 𝘚𝘵𝘢𝘱𝘩𝘺𝘭𝘰𝘤𝘰𝘤𝘤𝘶𝘴 𝘢𝘶𝘳𝘦𝘶𝘴 (11%) were the most common isolates. 𝘚𝘵𝘳𝘦𝘱𝘵𝘰𝘤𝘰𝘤𝘤𝘶𝘴 𝘶𝘣𝘦𝘳𝘪𝘴 is a dominant cause of clinical mastitis in New Zealand dairy cows but it is not commonly reported in dairy ewes overseas. Subclinical mastitis had a prevalence of 6.4%, which was substantially lower than the prevalence estimates reported in the EU, while recognising that variation in definitions and methods limits direct comparison. Milk samples collected from the randomly selected ewes had a geometric mean somatic cell count of 169,039 and a range of 2,000 to 34,953,000 cells/mL. The geometric mean somatic cell count was substantially higher than reports from European studies. Bacteria were isolated from 5.5% of the glands of randomly selected ewes, with the most common species being non-aureus staphylococci (4.0% of glands) and 𝘚. 𝘢𝘶𝘳𝘦𝘶𝘴 (0.6% of glands), consistent with the aetiology in the northern hemisphere. Moderate or severe teat end hyperkeratosis and udder asymmetry were confirmed as risk factors for subclinical mastitis. Although udder asymmetry is widely recognised as a clinical indicator of mastitis, this study provides, to our knowledge, the first published evaluation of the association in dairy sheep using a defined udder assessment protocol. A somatic cell count threshold of approximately 400,000 cells/mL had the greatest accuracy for diagnosing intramammary infection, but while it had a specificity of 0.88, its sensitivity was only 0.64. Mean log₁₀ somatic cell count increased linearly with rapid mastitis test score but its agreement was only moderate (Kendall’s tau = 0.47). Elevated rapid mastitis test score and somatic cell count, positive milk culture and subclinical mastitis were identified risk factors for elevated ewe-level aerobic plate count. Bulk milk somatic cell count had a geometric mean of 659,491 cells/mL, which was in the mid-range of estimates from overseas studies, while bulk milk aerobic plate count exceeded 100,000 CFU/mL in 22.3% of consignments, peaking in August. High bulk milk aerobic plate count was not well predicted by somatic cell count. Clinical mastitis incidence, subclinical mastitis prevalence, and bulk milk quality targets were set based on the means of the best performing quarter of farms. This thesis provides the first nationally representative mastitis and milk-quality baseline for New Zealand dairy sheep. It has confirmed that New Zealand dairy sheep mastitis is low-frequency but high-impact, with clinical cases concentrated around lambing with the potential for severe outcomes and poor prognoses. 𝘚𝘵𝘳𝘦𝘱𝘵𝘰𝘤𝘰𝘤𝘤𝘶𝘴 𝘶𝘣𝘦𝘳𝘪𝘴 is a relatively prominent cause of clinical mastitis among New Zealand dairy ewes compared to dairy ewes overseas. This shifts prevention efforts to early-lactation environmental control. Subclinical mastitis is caused by similar bacteria to overseas but the prevalence is low in New Zealand’s relatively extensive, machine-milked systems, suggesting a structural advantage worth protecting as the industry intensifies. Mastitis should be considered when managing high bulk milk aerobic plate count, but the relationship between somatic cell count and aerobic plate count at the bulk milk level is too weak for somatic cell count to serve as a management proxy. Currently, surveillance and decision-making are constrained more by data infrastructure than biology, making milk recording and repeat somatic cell count /rapid mastitis test protocols the most immediate area to develop on farm. Using this baseline information, future research can now be prioritised to address gaps, particularly in relation to causality, risk factors and diagnosis.
Keywords: dairy; sheep; mastitis; somatic cell count; aerobic plate count; intramammary infection; bulk milk; milk quality; udder conformation; clinical mastitis; subclinical mastitis; udder health; Mastitis; New Zealand; Diagnosis; Ewes; Udder; Diseases; Sheep milk; Composition; 30 Agricultural, veterinary and food sciences::3009 Veterinary sciences::300905 Veterinary epidemiology; 30 Agricultural, veterinary and food sciences::3009 Veterinary sciences::300907 Veterinary medicine (excl. urology)